Activation of mTORC1 in Collecting Ducts Causes Hyperkalemia - Chen, Zhenguo (American Society of Nephrology, 2014)
Mutation of TSC (encoding tuberous sclerosis complex protein) and activation of mammalian target of rapamycin (mTOR) have been implicated in the pathogenesis of several renal diseases, such as diabetic nephropathy and polycystic kidney disease. However, the role of mTOR in renal potassium excretion and hyperkalemia is not known. We showed that mice with collecting-duct (CD)–specific ablation of TSC1 (CDTsc1KO) had greater mTOR complex 1 (mTORC1) activation in the CD and demonstrated features of pseudohypoaldosteronism, including hyperkalemia, hyperaldosteronism, and metabolic acidosis. mTORC1 activation caused endoplasmic reticulum stress, columnar cell lesions, and dedifferentiation of CD cells with loss of aquaporin-2 and epithelial-mesenchymal transition-like phenotypes. Of note, mTORC1 activation also reduced the expression of serum- and glucocorticoid-inducible kinase 1, a crucial regulator of potassium homeostasis in the kidney, and decreased the expression and/or activity of epithelial sodium channel-α, renal outer medullary potassium channel, and Na(+), K(+)-ATPase in the CD, which probably contributed to the aldosterone resistance and hyperkalemia in these mice. Rapamycin restored these phenotypic changes. Overall, this study identifies a novel function of mTORC1 in regulating potassium homeostasis and demonstrates that loss of TSC1 and activation of mTORC1 results in dedifferentiation and dysfunction of the CD and causes hyperkalemia. The CDTsc1KO mice provide a novel model for hyperkalemia induced exclusively by dysfunction of the CD.